CORRELATION PORTRAIT AS A MEANS TO STUDY THE RELATIONSHIPS OF FOLLICULAR THYROCYTES ULTRASTRUCTURES: THE PROFILE OF TRANSPORT CAPABILITY UNDER THE ACTION OF ORGANIC IODINE IN THE CONDITIONS OF ALIMENTARY IODINE DEFICIENCY - Ryabukha, O.I. (Medical Informatics and Engineering, 2022)
Background. The use of mathematical methods to study the morpho-functional features of follicular thyrocytes ultrastructures of the thyroid gland, in particular the transport direction of its activity, is due to the importance of the thyroid gland for the body. Impairment of synthesis, transporting, deiodinizing, thyroid hormones metabolism lead to clinical and subclinical disorders of the thyroid gland. The share of thyroid pathology in the overall structure of endocrine morbidity is significant and is characterized by a tendency to increase. The most common cause of thyroid disorders is alimentary iodine deficiency and related health disorders; a good reason is the impairment of thyroid homeostasis by various harmful effects of chemical or physical nature. Prevention of iodine deficiency disorders and correction of their manifestations is carried out with iodine-containing substances. Organic compounds are increasingly used, among which seaweed is considered to be a particularly promising source of organic iodine. The purpose of the study was to elucidate the relationship between the follicular thyrocytes ultrastructures in the transport direction of their activity when taking organic iodine under conditions of potentiation of iodine deficiency in the diet with antithyroid drugs. Material and methods. The study was performed on 50 white nonlinear male rats with initial weight of 140-160 g, of which 10 animals consumed common digestible food, 40 - iodine-deficient starch-casein diet. Potentiation of alimentary iodine deficiency was performed with mercazolyl (Thiamazole) at the dose of 3 mg per kg body weight. Correction during 30 days of potentiated alimentary iodine deficiency was performed by histologically determined small (initial - 21 |jg iodine per kg body weight), moderate (50 jg iodine per kg body weight) and large (100 jg iodine per kg body weight) doses of organic iodine of iodine-protein components from the Black Sea red alga Phyllophora nervosa (DC.) Grev. The tasks were solved by electron microscopy, method of semi-quantitative analysis of electronograms, method on specifying the profiles of special capabilities of hormone-poietic cells, correlation analysis with determining the strength of connections on the Chaddock scale and designing of correlation portraits; interpretation of the obtained results was performed from the standpoint of cytophysiology. Results and discussion. Analysis of correlation portraits revealed that in the conditions of uncorrected potentiated alimentary iodine deficiency, despite the impairment of the microcapillary bed, there is a certain resource for transportation of the produced hormonal product. Intake of organic iodine improves intraorgan hemocirculation. Features of exposure to small doses of organic iodine are such mechanisms of adaptation to the transport of thyroid hormones in adverse conditions as the presence of stasis and microthrombosis in the microcapillary bed, increased folding of follicular thyrocytes' basal cytoplasmic membranes, endothelial hypertrophy, increasing the number of endothelial cells and their pseudopodia. Taking moderate and large doses of organic iodine in the discussed conditions brings closer to the characteristics of intact animals such components of the transport profile as folding of the basal cytoplasmic membranes of follicular thyrocytes, the state of endothelial cells and their pseudopodia, the state of the microcapillary bed. The main difference between the effects of moderate and large doses of organic iodine is the peculiarities of the pericapillary space, which when taking a moderate dose is characterized by the absence of inclusions, and when taking a large dose by its moderate (normal) width. Thus, when correcting the potentiated alimentary iodine deficiency with organic iodine, the dependence is established of the components of follicular thyrocyte transport capability profile's characteristics and the relationships between them on the fact of iodine-containing compound. An important result of the effect is the improvement of the morpho-functional state of the follicular thyrocytes' basal cytoplasmic membranes and optimization of connections between the constituent elements of the profile. The direction and depth of changes depend on the dose of iodine consumed: the condition of the profile elements and the relationships between them improved with increasing iodine intake. Conclusions. The study of the effects of biological substances that can both potentiate and "mitigate" the phenomena of iodine deficiency, requires the joint efforts of scientists in various specialties, in particular, using appropriate mathematical approaches. Correlation portraits are an informative tool for studying the transport direction of follicular thyrocytes of the thyroid gland. Under conditions of uncorrected potentiated alimentary iodine deficiency, there is a certain resource for transportation of the produced hormonal product by the microcapillary bed of the thyroid gland. Intake of organic iodine against the background of potentiated alimentary iodine deficiency improves the condition of the microcapillary bed of the thyroid gland. Improvement of the hemocirculation of the microcapillary bed in the thyroid gland when taking different doses of iodine under conditions of alimentary iodine deficiency potentiation is provided by various ultrastructural components of the follicular thyrocytes' transport capability profile. The intake of moderate and large doses of organic iodine by rats under the conditions of alimentary iodine deficiency potentiation brings the state of the microcapillary bed in their thyroid glands closer to the characteristics of intact animals.